2020
DOI: 10.3390/su12030765
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Dairy Sustainability with Integrated Crop–Livestock Farming

Abstract: Dairy farms are predominantly carbon sources, due to high livestock emissions from enteric fermentation and manure. Integrated crop–livestock systems (ICLSs) have the potential to offset these greenhouse gas (GHG) emissions, as recycling products within the farm boundaries is prioritized. Here, we quantify seasonal and annual greenhouse gas budgets of an ICLS dairy farm in Wisconsin USA using satellite remote sensing to estimate vegetation net primary productivity (NPP) and Intergovernmental Panel on Climate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…In our previous work, we applied aircraft-based mass balance to quantify facilitylevel emissions for concentrated animal feeding operations in the Upper Midwest and found (as here) good topdown/bottom-up agreement for enteric emissions but discrepancies for manure (Yu et al, 2020). A recent site-level study at a large Wisconsin dairy farm observed low manure emissions (~30% of the enteric flux) owing to frequent field application throughout the year (Wiesner et al, 2020), further supporting our characterization of manure management as a key uncertainty in current large-scale bottom-up inventories.…”
Section: Livestock Methane: Enteric Emissions Well-represented But Lamentioning
confidence: 54%
“…In our previous work, we applied aircraft-based mass balance to quantify facilitylevel emissions for concentrated animal feeding operations in the Upper Midwest and found (as here) good topdown/bottom-up agreement for enteric emissions but discrepancies for manure (Yu et al, 2020). A recent site-level study at a large Wisconsin dairy farm observed low manure emissions (~30% of the enteric flux) owing to frequent field application throughout the year (Wiesner et al, 2020), further supporting our characterization of manure management as a key uncertainty in current large-scale bottom-up inventories.…”
Section: Livestock Methane: Enteric Emissions Well-represented But Lamentioning
confidence: 54%
“…Harvest NEP was then compared to annual sums of (a) RS NEP without improvements (RS Lit ), (b) ERF NEP, and (c) improved RS NEP (RS ERF ). Finally, we estimated farm emissions following Wiesner et al (2020), to calculate the farm-scale GHG balance for 2019. Please refer to the Supporting Information S1 for a detailed description of emission calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Harvest biomass was weighed and stored on site, except for winter wheat harvests, 53% of dry corn kernels, and 22% of soybean harvests, which were sold (Table 3). We used harvest index data (HI; established from personal conversation with the farm manager; Wiesner et al., 2020), dry matter fractions (Table S1 in Supporting Information ), and root to shoot ratios from the literature (Agostini et al., 2015; Bolinder et al., 2007; IPCC, 2006; Little et al., 2017; Saggar et al., 2015) to calculate NEP Harvest . To check whether literature values for root:shoot and dry matter mass would bias our results, we calculated harvest NEP using data from a 2019 field campaign, where aboveground and belowground biomass were collected at three different time points during 2019 (May, July and September).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the cutting frequency of forage crop was often overlooked, despite being an important factor in forage harvesting or simulated grazing. There have been some important reports on GHG emission inventories from sources of ruminant agriculture based on emission factor methods [16,17] or remote sensing [18], and more field trials are worth implementing in localized emission factor studies. Moreover, studies on the emissions of the three dominant components of GHGs, global warming potential, and the mechanisms of different forage crops should be conducted under a combination of ingestion, excrement, and trampling of grazing livestock, which could be simulated by multi-cutting and animal excrements to a certain extent [19][20][21].…”
Section: Introductionmentioning
confidence: 99%